Linguistic And Practical Research of Social Network Correspondence - Rahimkulova Lobar Hamro qizi (International Journal Of Literature And Languages, 2025)
Social networks, their emergence, types and significance are a process that has been studied by scientists for several years. When we take a scientific approach to the connection of social networks with other areas and their practical significance, we witness that they are of great importance for all areas. An approach to social networks from the point of view of applied linguistics is of great importance. The Internet is a social creation rather than a technical creation. Indeed, despite the amazing results and the visual shelter of the screen presentation, what is very clear when dealing with any of the functions of the Internet is its linguistic character. If the Internet is a revolution, then it can be a linguistic revolution. [1:10]. When using the Internet, social networks, people use linguistic and paralinguistic units as the main means of communication. Language is a product of thought, a means of socio-spiritual communication. Therefore, social networks are not a technical innovation, but a social innovation, as D. Crystal noted, if there is a revolution, then it is not a technical, but a social revolution.